The Relationship between Characteristics of Cerebospinal Fluid and Tuberculous Meningitis detected using Real Time PCR - Masfiyah, Masfiyah; Subakir, Subakir; Kristina, Tri Nur (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2016)
Introduction: Tuberculosis (TB) carries a high morbidity and mortality, however, its diagnosis can be difficult due to low concentration of bacteria in the cerebrospinal fluid (CSF). Although increased CSF protein, decreased CSF glucose; cerebrospinal fluid (CSF) pleocytosis with mononuclear cells predominance are commonly used to diagnose TB infection, they show inconsistent results.Objectives: To analyze the relationship between several characteristics of the CSF and TB meningitis.Methods: This is an observational research, with a cross sectional design, 27 patients with TB meningitis and or meningoencephalitis with Thwaites diagnostic score â‰¤ 4 obtained from mecidal records. The definitive diagnosis of TB meningitis was made using the Ziehl Neelsen (ZN) staining and or culture TB, or polymerase chain reaction (PCR) amplification with the target in IS6110, Ziehl-Neelsen staining (ZN) culture method. Characteristics of CSF including increased CSF protein, decreased CSF glucose, cerebrospinal fluid (CSF) pleocytosis with mononuclear cells predominance and the CSF abnormalities were evaluated in the laboratory of molecular microbiology of Medical Faculty, Diponegoro University/dr Kariadi General Hospital, Semarang. The statistical analysis used was prevalent ratio (RP).Results: Over 27 patients, 12 (44.4%) were diagnosed with definite TB meningitis. Statistical analysis showed that prevalence ratio of the increased levels of protein CSF was 3.143 (95% CI: 0.502 to 19.692), decreased glucose levels was 1.750 (95% CI: 0.501 to 6.112), pleocytosis with a predominance of mononuclear cells was 2.5 (CI 95% : 1.238 to 5.048), whereas the CFS abnormality was RP 2.2 (95% CI: 1.087 to 4.454).Conclusion: This study has shown that pleocytosis with mononuclear cells predominance and CFS abnormalities have a positive relationship with definite TB meningitis.